This is my religious duty”: Ayatollah Khomeini’s political debut in 1962 - Baranov, Alexey V. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2022)
The article examines the events of October – December 1962 in Iran, related to the discussions that took place in Iranian society on the issue of the election bill, as part of the preparation of the reforms of the “White Revolution of the Shah and the People”. Based on the analysis of Ayatollah Khomeini’s speeches and appeals, his views and approaches to the proposed bill are characterized. Based on the results of the analysis, it is concluded that Ayatollah Khomeini’s approach to the Shah’s initiative is unconstitutional and anti-Islamic. The Shah’s refusal to ratify the bill meant recognition of Khomeini as the leader of the anti-Shah movement in Iran.